EFEKTIVITAS KONSELING KELOMPOK DENGAN TEKNIK SELF MANAGEMENT UNTUK MENGURANGI PERILAKU PROKRASTINASI AKADEMIK SISWA DI SMA NEGERI 3 TARAKAN - Yospina, Yospina; Pribadi, Hendra (Jurnal Bimbingan dan Konseling Borneo, 2019)
The formulation of the problem in this study is whether group counseling with self management techniques is effective to reduce students? academic procrastination behavior at Tarakan 3 public high school. This study aims to determine how effective group counseling with self management techniques is to reduce students? academic procrastination behavior at Tarakan 3 public high school.This type of research is a quantitative approach that is experiment. This study uses an untreated control group design with dependent pretest and posttest design. The population in this study is 143 class XI students at SMA Tarakan and a sample of 20 class XI students in SMA Tarakan. Data collection methods in this study use the scale of academic procrastination with likert scale. Data analysis techniques in this study are descriptive statistical techniques and test hypotheses using MIXED ANAVA assisted by SPSS 24.0 for windows program. Based on the results of the study before and after the treatment, obtained the results of calculation of hypothesis testing by looking at the table subject effect obtained F value = 157.370 and p value = 0,00 (p<0,05) and in the table pairwise comparisons shows that in the experimental group is significant (MD=-19.600; p<0,05) and in the control group showed that is was not significant (MD=- 2.400; p>0,05). Based on the results of mixed anova (anava mixed design) test management using SPSS 24.00 for windows it can be coucluded that group counseling with self management techniques can reduce students? academic procrastination behavior at Tarakan 3 public high school. Keyword: group counseling, self management, academic procrastination